Integrative network pharmacology, metabolomics and gut flora studies reveal mechanisms of action of Rhododendron molle (Blume) G. Don to ameliorate liver injury - Jiang, Xiaolei; Zhuang, Yafeng; Meng, Tiancheng; Meng, Tianwei; Li, Xinghua; He, Dan; Meng, Hongyu; Chang, Hong (Frontiers in Microbiology, 2025)
BackgroundLiver injury (LI) is responsible for a significant number of fatalities each year. In the context of Mongolian medicine, Rhododendron molle (Blume) G. Don (RM) is utilized for its properties to treatment of hepatic disorders. However, the underlying mechanisms of its action remain poorly understood.ObjectivesClarifying the process through which RM enhances LI.MethodsThe chemical constituents were subjected to analysis, and network pharmacology alongside molecular docking studies were conducted. Additionally, ELISA, staining techniques, metabolomic analyses, and 16S rDNA sequencing were performed.ResultsA total of 17 components have been identified from RM, including liver disease-related compounds such as kaempferol, emodin, quercetin. Network pharmacology has identified notable genes that exhibit a strong binding affinity to active compounds, including emodin, which interacts with IL6 and PPARG, and aloeemodin, which binds to IL6 and AKT1. In a rat model of LI induced by CCL4, low dose (0.07875 g/kg) of RM demonstrated a reduction in ALT and γ-GT levels (p < 0.05). Metabolomic analysis indicated that RM has an impact on the concentrations of 13-OxoODE, morphine, and niacinamide in rat models exhibiting LI, simultaneously several metabolic pathways, including steroid biosynthesis, linoleic acid metabolism, and tryptophan metabolism. By integrating the findings from metabolomics with KEGG pathways, it was determined that RM may ameliorate LI by activating specific pathways and modulating fatty acid metabolic processes, particularly linoleic acid and arachidonic acid metabolism. Furthermore, low-dose RM (RML) was found to enhance beneficial gut microbiota such as Lactobacillus, suggesting its potential role in the regulation of intestinal homeostasis and barrier integrity.ConclusionRML has the potential to enhance the composition of intestinal microbiota by through the differential regulation of various metabolized components, including 13-OxoODE, morphine, and niacinamide, it influences several metabolic pathways, notably steroid biosynthesis, lysine degradation, interconversions of pentose and glucuronate, as well as the metabolism of linoleic acid. Additionally, it may promote the proliferation of HT002 and Lactobacillus probiotics, thereby contributing to the amelioration of LI. It establishes a robust foundation for future applications and the development of associated pharmaceuticals.